2011
DOI: 10.4067/s0717-95022011000300056
|View full text |Cite
|
Sign up to set email alerts
|

Metopismo: Bases Morfológicas, Implicancias Clínicas y Reporte de Caso

Abstract: RESUMEN:Durante la vida fetal y la infancia, los huesos planos de la bóveda craneal están separados por membranas densas de tejido conectivo que constituyen articulaciones fibrosas conocidas como suturas; las cuales tienen como objetivo durante los primeros estadios de la vida favorecer el desarrollo encefálico. Eventualmente estas suturas con el paso de los años se cierran formando una sinostosis entre los huesos del cráneo. Una de estas es la sutura frontal, que une los 2 huesos frontales en la época embrion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
3
0
2
Order By: Relevance
“…One of them is the metopic suture, which joins the two frontal bones in the embryonic period and in the newborn. This suture appears approximately at the end of the second month of intrauterine life between the two ossification centers of the frontal bone, and is considered an anterior extension of the sagittal suture, and its total fusion can occur from the end of the first year to the eighth or tenth year of life (ROA; MORAGA; CANTIN, 2011;KIMAPORN et al, 2015). It has been reported that in some cases this suture can persist into adulthood, closing much later than the rest of the other sutures, even in very old people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is the metopic suture, which joins the two frontal bones in the embryonic period and in the newborn. This suture appears approximately at the end of the second month of intrauterine life between the two ossification centers of the frontal bone, and is considered an anterior extension of the sagittal suture, and its total fusion can occur from the end of the first year to the eighth or tenth year of life (ROA; MORAGA; CANTIN, 2011;KIMAPORN et al, 2015). It has been reported that in some cases this suture can persist into adulthood, closing much later than the rest of the other sutures, even in very old people.…”
Section: Introductionmentioning
confidence: 99%
“…Different classifications according to layout and shape were described, thus allowing complete and incomplete metopic sutures. Complete suture extends from the nasion to the bregma uninterruptedly, and incomplete when it extends from the nasion or bregma to several points of the frontal bone, and is classified into two subtypes: incomplete metopic suture "bregma" and incomplete metopic suture "nasium" (ROA; MORAGA; CANTIN, 2011;KIMAPORN et al, 2015). Regarding the frequency of metopism, it is known that ethnic diversity plays an important role in the different incidences of metopism, and it is reported that this situation varies from 0.8% to 15% in different populations (NIKOLOVA; TONEVA, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The metopic suture joins the two frontal bones (Figure 1), is a fibrous suture-type joint that extends from the nasion to the bregma, they begin to ossify at approximately eight weeks of gestation, until the two frontal bones fuse approximately two years [2], the other sutures (coronal, sagittal, and lambdoid) are closed much later. However, the metopic suture sometimes does not close during childhood and continues into adulthood, as a joint that separates the frontal bone into two symmetrical halves.…”
Section: Introductionmentioning
confidence: 99%
“…Uma delas é a sutura metópica, que une os dois ossos frontais no período embrionário e no recém-nascido. Esta sutura surge aproximadamente no final do segundo mês de vida intrauterina entre os dois centros de ossificação do osso frontal sendo considerada como uma extensão anterior da sutura sagital e sua fusão total pode ocorrer desde o final do primeiro ano até o oitavo ou décimo ano de vida (ROA; MORAGA; CANTIN, 2011;KIMAPORN et al, 2015). Tem sido relatado que em alguns casos esta sutura pode persistir na idade adulta, fechando muito mais tarde do que o resto das outras suturas, mesmo em pessoas muito idosas.…”
Section: Introductionunclassified
“…Diferentes classificações de acordo com o layout e a forma foram descritas, podendo assim encontrar suturas metópicas completas e incompletas. Sutura completa, se estende do násio ao bregma de forma ininterrupta, e incompleta quando se estende do násio ou do bregma a vários pontos do osso frontal, sendo classificada em dois subtipos: sutura metópica incompleta "bregma" e sutura metópica incompleta "násio" (ROA; MORAGA; CANTIN, 2011;KIMAPORN et al, 2015). Com relação a frequência do metopismo, sabe-se que a diversidade étnica desempenha papel importante nas diferentes incidências do metopismo, sendo relatado que esta situação varia de 0,8% a 15% em diferentes populações (NIKOLOVA; TONEVA,2012).…”
Section: Introductionunclassified